The Influence of Compentency and Compensation on Teacher Performance at SMK Budi Mandiri Tanjungsari - Ermi Triaji; Fachril Fachrurozi (Jurnal Dialektika: Jurnal Ilmu Sosial, 2025)
This study aims to test and analyze the influence of competence and compensation on teacher performance at SMK Budi Mandiri Tanjungsari (case study on teachers at SMK Budi Mandiri Tanjungsari) which is an educational institution. The method used was a quantitative method with a descriptive approach. The research population was all teachers at SMK Budi Mandiri Tanjungsari, a total of 40 people. Data were collected through a questionnaire using a Likert scale, then analyzed using multiple linear regression tests using the SPSS 25 program. The results of the study show that, 1) Competence has a positive and significant influence on the performance of teachers at SMK Budi Mandiri Tanjungsari with a value of 73.9%. 2) Compensation has a positive and significant influence on the performance of Teachers at SMK Budi Mandiri Tanjungsari with a value of 70.8%. The magnitude of the total influence of the Competence and Compensation variables on the Performance of Teachers at SMK Budi Mandiri Tanjungsari is indicated by the magnitude of the determination coefficient r² = 0.706 or 70.6%, while the external influence or error is 29.4%.